Preventing cognitive decline and dementia from cerebral small vessel disease: The LACI-1 Trial. Protocol and statistical analysis plan of a phase IIa dose escalation trial testing tolerability, safety and effect on intermediary endpoints of isosorbide mononitrate and cilostazol, separately and in combination - Blair, Gordon W.; Appleton, Jason P.; Law, Zhe Kang; Doubal, Fergus; Flaherty, Katie; Dooley, Richard; Shuler, Kirsten; Richardson, Carla; Hamilton, Iona; Shi, Yulu; Stringer, Michael; Boyd, Julia; et al. (Sage, 2018)
Rationale